Time trends in lipid lowering drug use in The Netherlands. Has the backlog of candidates for treatment been eliminated? - Mantel-Teeuwisse, Aukje K (Blackwell Science Inc, 2002)
AIMS: To assess time trends in lipid lowering drug use in The Netherlands. METHODS: Data were obtained from the PHARMO-database, comprising pharmacy records of approximately 300000 people in The Netherlands. In the period from 1991–98, we estimated prevalence of lipid lowering drug use on the first Wednesday of October. A patient was defined as incident user if (s)he filled a prescription for lipid lowering medication after a 360 days lipid lowering drug free interval. Both prevalence and incidence estimates were weighted for the sex and age distribution of the general Dutch population. RESULTS: From 1991 to 1998, the prevalence of lipid lowering drug use increased from 0.5% (95% confidence interval (CI): 0.5, 0.6) to 2.3% (95% CI: 2.2, 2.4) in women and from 0.6% (95% CI: 0.6, 0.6) to 2.9% (95% CI: 2.8, 3.0) in men. Prevalence increased with increasing age and was highest in the age category 60–69 years (in 1998: 9.9% (95% CI: 9.4, 10.4) in women and 11.6% (95% CI: 11.0, 12.1) in men). In 1992, the estimated incidence of lipid lowering drug use was 251(95% CI: 226, 277)/100000 person years in women and 251(95% CI: 225, 276)/100000 person years in men. The largest incidence estimates were observed in 1996 (685(95% CI: 644, 726)/100000 person years in women and 881(95% CI: 834, 928)/100000 person years in men). After 1996, incidence stabilized in 1997 and decreased in 1998 to 599(561, 637)/100000 person years in women and 731(688, 773)/100000 person years in men. Most of the patients (approximately 95%) were treated with one lipid lowering agent. Statins were used by over 90% of patients from 1996 onwards. In 1998, 35% of the patients started with a statin that was not a first choice drug (mainly atorvastatin). CONCLUSIONS: In the period from 1991–98, prevalence of lipid lowering drug use significantly increased in The Netherlands. However, incidence stabilized and decreased after 1996 which may be explained by the fact that the number of patients eligible for treatment was reached. The question remains whether lipid lowering medication was targeted to the appropriate patients.